Using strain typing to characterise a fluoroquinolone-resistant Neisseria gonorrhoeae transmission network in southern California. Issue 4 (13th March 2008) - Morris, S R; Knapp, J S; Moore, D F; Trees, D L; Wang, S A; Bolan, G; Bauer, H M
Abstract : Objective: We investigated the initial outbreak of fluoroquinolone-resistant Neisseria gonorrhoeae (QRNG) in southern California with analysis of transmission using strain typing. Methods: Surveillance for QRNG was conducted between 2000 and 2002 in southern California, including epidemiology and strain typing by a combination of antibiogram, auxotype, serovar, Lip type and amino acid alteration patterns in the quinolone-resistance determining region of GyrA and ParC. Combining epidemiological data with strain typing, we describe the emergence of QRNG outbreak strains using risk factor analysis and transmission networks. Results: Two outbreak strains accounted for 82% of isolates. Both strains required proline, were Lip type 17c, had amino acid alterations 91> Phe in GyrA and 87> Arg in ParC, but they differed by their serovar, IB-3C8 versus IB-2H7, 2G2. Outbreak strains were positively associated with men who have sex with men (MSM), adjusted odds ratio (AOR) 23.9 (95% confidence interval (CI) 2.2 to 261) and negatively associated with travel history: AOR 0.05, (95% CI 0.0 to 0.6). Network analysis demonstrated that 17 cases were connected by sexual contacts and/or public venues including bars, bathhouses/sex clubs, and internet sites. Conclusions: QRNG may have become established among Californian MSM through an identified transmission network of southern Californian bars, bathhouses and internet sites.